Description of Fatigue Sensitivity Curves and Transition to Critical States of Polymer Composites by Cumulative Distribution Functions (Fracture and Structural Integrity, 2022)
In this paper, a novel model is presented to describe the composite mechanical properties degradation during cyclic loading. The model is based on cumulative distribution functions using. Weibull probability distribution law and beta distribution are considered. The dependences of the fatigue sensitivity coefficient on the preliminary cyclic exposure are derived. The damage value function derivative using is proposed to define damage accumulation stages boundaries. Model parameters are obtained using experimental data. Determination coefficients are calculated. A high descriptive capability is noted. Rationality and expediency of using cumulative distribution functions as the approximation of experimental data on mechanical characteristics reduction after preliminary cyclic exposure is concluded.
Keywords: Composite; Damage accumulation; Mechanical properties degradation; Cumulative distribution functions